LASER LEVELING OF SOIL IN THE PRE-SEASON PERIOD FOR LEVELING SOIL RELIEF IN «THE TST AGRO CLUSTER «NIZHNECHIRCHIK» DISTRICT TASHKENT REGION» - Professor., G’ulomov Saidasror Sayidaxmedovich; Head Teacher., Rasulova Muxabbat Tishabayevna (Scholar Express Journals, 2023)
This article presents methods for leveling the soil before the pre-sowing period using laser leveling in the Nizhnechirchik district of the Tashkent region.
Keywords: leveling; laser; cluster; digital shooting; laser planning